Features of the Professional Well-Being of Information Technologies Employees - Kovalenko, Alla; Ryk, Hanna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article presents the results of theoretical and empirical research on IT workers’ professional well-being. Professional well-being is defined as an integral concept that includes both positive and negative factors that develop independently, as a psychological state of the employee, associated with the efficiency of his work and the satisfaction of life in general. The results of the empirical study revealed that the average level of professional well-being of IT workers prevails. It was found that most workers have a medium level of autonomy, some freedom in activities, and feel competent to change the professional environment. For them, the opportunity for professional growth is essential. The presence of professional goals that correlate with their values means improving their professional self. The most crucial professional well-being components of IT workers are professional growth, the formation of professional goals, and positive relationships in the workplace. The correlation analysis results showed that the experience has a positive effect on professional well-being and attitude to oneself as a professional. Professional autonomy is formed on experience, a sense of demand for activities, and positive reinforcement of the work results. Freedom of action is an integral feature of a professionally developed professional. Professional competence is acquired in the course of professional activity, and at the same time, the professional well-being of the specialist, the success of activity, and authority increase. Positive relationships with the team and colleagues’ attitude to the employee as a professional are essential for professional well-being. The critical construct of IT workers’ professional well-being is professional growth as the main predictor of job change. Professional demand is a motive for self-realization in the profession. The work results allow the specialist to feel like a professional and a member of a particular reference group.
Keywords: professional well-being; organizational commitment; professional demand; professional growth; professional competence; experience; IT workers